Echa ŚDM 2016 w Krakowie w prasie włoskiej – perspektywa młodzieży - Stańkowski, Bogdan (Studia Pastoralne, 2026)
The article briefly discusses the situation of Italian youth from a sociological perspective. An analysis of the available literature of the subject was used to outline some of the phenomena among the young people seen in the following dimensions: religiousness, work, school, family. The research based on content analysis of selected italian scientific journals was conducted in 2017. The author tries to answer the question about the echoes of World Youth Day Krakow 2016 which can be observed in scientific studies in Italy. Three detailed research questions were proposed.